Using indices of species' potential range to inform conservation status. (April 2021) - Mason, Tom H.E.; Stephens, Philip A.; Gilbert, Gillian; Green, Rhys E.; Wilson, Jeremy D.; Jennings, Kate; Allen, Judy R.M.; Huntley, Brian; Howard, Christine; Willis, Stephen G.
Highlights: We present an index that contrasts realised and potential ranges. We modelled potential ranges that would exist in absence of human impacts. Species with wider potential ranges may warrant higher conservation prioritisation. Our index allows the status of species' distributions to be assessed consistently. Abstract: Assessments of conservation status are typically based on short-term extinction risk, but the value of indicators that compare the current state of species (e.g., abundance or distribution) to potential baselines is increasingly recognised. The use of baselines in conservation legislation is hindered by ambiguity in how baselines should be determined and interpreted, leading to inconsistent application. Here, we explored the use of species' potential ranges as a consistent means of quantifying baselines for assessing species' distributions, a key component of conservation status. Using breeding birds of Great Britain (GB) as a case study, we simulated where bird species would be expected to occur today in a modelled world without human land use. We calculated indices that contrasted these potential human-free ranges with realised ranges. Our analyses revealed that 42% of GB birds have wider realised than potential ranges and 28% have narrower realised than potential ranges. These indices could lead to reassessments of current conservation priorities. Eighteen species assigned 'least concern' status by the GB regional IUCN Red List had much narrower realised than potential ranges, suggesting that their ranges are in a more degraded state than currently recognised by Red List criteria. Some of these species are not under active conservation management and could be candidates for higher prioritisation. Our approach provides a systematic means of quantifying range baselines that is not reliant on variable historic data or expert opinion and, thereby, provides a step forward in resolving a major contemporary problem in conservation assessment: how to set baselines in conservation consistently. The insights produced are also of wider scientific and cultural relevance, revealing where species would likely exist today in the absence of historic human impacts. This could be used to identify areas where targeted restoration actions might lead to the return of historically extirpated species, or even to novel colonists.